Chemical Composition and Biological Activity of Commelina erecta: An Edible Wild Plant Consumed in Brazil - Lucas Vinicius Cavichi; Ângela Liberal; Maria Inês Dias; Filipa Mandim; José Pinela; Marina Kostić; Marina Soković; Daneysa Lahis Kalschne; Ângela Fernandes; Cristiane Canan; Lillian Barros; Joana S. Amaral (Foods, 2023)
In recent years, the interest in products of natural origin has boosted the exploitation and use of plants as food and sources of bioactive compounds, especially wild plants widely used in different cultures for several purposes. Commelina erecta is a wild edible plant (WEP) traditionally used as food and medicine, about which few studies exist. Thus, this study aimed at enhancing the knowledge about its nutritional, chemical and bioactive profile, considering different plant parts and development stages, in order to increase its inclusion in the diet of South American communities. The nutritional profile was found to be similar to other WEP frequently consumed in Brazil. Thirteen phenolic compounds (HPLC-DAD-ESI/MS) were tentatively identified, with apigenin, luteolin and quercetin derivatives being the most abundant. Fructose and oxalic acid were the major sugar and organic acid, respectively, in the aerial parts of C. erecta, and four isoforms of tocopherols were also identified. Regarding the plant’s antioxidant activity, the EC50 values varied between 18.4 and 1060 µg/mL in the inhibition of lipid peroxidation assay (TBARS) and between 53 and 115 µg/mL in the oxidative haemolysis inhibition (OxHLIA) assay. The hydroethanolic extract obtained from stems at the flowering stage also presented anti-inflammatory activity. In general, all the extracts evidenced promising antimicrobial activity. Altogether, these results reinforce the traditional use of this plant species as food and medicine to support the diet of needier populations and also promote food sovereignty and sustainability.